The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.4269/ajtmh.16-0396
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Sickle Cell Trait Status: A Cross-Sectional Survey of Antenatal Women in Ghana

Abstract: Abstract. This study was conducted to evaluate pregnant women's awareness of sickle cell disease and sickle cell trait and the factors that contribute to it. Two hundred and six pregnant women with at least 20 weeks gestation answered a questionnaire regarding awareness of their trait status and questions to test their knowledge of sickle cell disease. Although the majority of patients were aware of their trait status (87.4%), only 29% of knowledge questions were answered correctly; patients who self-identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…27 Although complex, the HbAS variant offers a protective advantage to infections common in our set up, such as infection with Plasmodium species, 6 , 28 – 30 and this risked 25% of the next generation to acquire HbSS if genetic counseling and testing is not emphasized. 21 , 22 Further, findings from our study have indicated an information gap regarding the existence of the sickle cell defects, similar to what has been reported by other studies. 7 , 9 , 10 Lack of awareness may portend the effort to lessen the risk of genetic cross-over that could multiply the trait incidence as well as the number of individuals who may inherit the sickle cell disease.…”
Section: Discussionsupporting
confidence: 90%
“…27 Although complex, the HbAS variant offers a protective advantage to infections common in our set up, such as infection with Plasmodium species, 6 , 28 – 30 and this risked 25% of the next generation to acquire HbSS if genetic counseling and testing is not emphasized. 21 , 22 Further, findings from our study have indicated an information gap regarding the existence of the sickle cell defects, similar to what has been reported by other studies. 7 , 9 , 10 Lack of awareness may portend the effort to lessen the risk of genetic cross-over that could multiply the trait incidence as well as the number of individuals who may inherit the sickle cell disease.…”
Section: Discussionsupporting
confidence: 90%
“…Among the 300 participants who were screened for SCD, none knew of her SCD status prior to screening in the current study, including one participant who was found to be Hb-SS. This level of knowledge of personal SCD status is very low compared to that reported by Obed et al in Ghana where 10% of pregnant women self-reported sickle cell trait, and that reported by Treadwell et al where 16% reported knowledge of their sickle cell trait status ( Treadwell et al, 2006 ; Obed et al, 2017b ). Also, in a study of 147 African-American patients aged 18–50 years seen in an emergency department, 31% knew of their own trait status ( Burnham-Marusich et al, 2016 ).…”
Section: Discussionmentioning
confidence: 60%
“…This was again the same as other studies conducted in Nigeria which showed that higher level of education and knowing a relative with SCD or sickle cell trait was significantly associated with high knowledge of SCD (disease; Ezenwosu et al, 2021 ). Another study done by Obed et al showed that respondents with at least secondary education scored an average one point higher on the knowledge test than those with lower education, and knowing someone with SCD was associated with a higher level of knowledge than in individuals who did not know any affected individual ( Obed et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education is particularly important when programs and ideas are new and in relatively low literacy settings. A number of studies in various settings in Africa have demonstrated the lack of knowledge about NBS and the specific diseases screened, not only among parents (Obed et al 2017;Aderotoye-Oni et al 2018) but also among health professionals (Adegoke et al 2018). Family advocacy experts from the US discussed not only the need for parent and professional education, but also the need for parent involvement in policyand decision-making activities related to NBS (Evans et al 2018;Forman et al 2013).…”
Section: Other Topics Discussedmentioning
confidence: 99%